Analysis of the possibilities of improving environmental conditions in lecture halls using mechanical ventilation - Grzebielec, Andrzej; Szelągowski, Adam; Bruzi, Krzysztof (International Conference “Environmental Engineering”, 2020)
Didactic classes are conducted in lecture halls usually adapted from the technical side to present content. Audiovisual and sound systems are installed. Unfortunately, in many cases, classrooms are designed from the point of view of air conditioning and ventilation, just like office rooms. As a result, during classes, even in rooms where air conditioning occurs, the conditions change so unfavourably that both teacher and students experience discomfort. The work analyzes the change in temperature, CO2 concentration, PM2.5 concentration and relative humidity in the room, where heat gains from people and equipment as well as moisture gains exceed design values. The work uses a channel-free Respireco recuperator with cyclic operation. First, the thermodynamic properties of the recuperator itself were checked, and then it was tested in a selected Polish primary school. The results show that this type of recuperators are able to provide correct indoor climatic conditions in lecture halls. The use of mechanical ventilation using a recuperator with a ceramic heat recovery caused the CO2 concentration in the room to drop by 50% during classes. However, PM2.5 concentration was maintained at a level three times lower than in a room without mechanical ventilation. It should therefore be concluded that the use of mechanical ventilation with recuperation not only reduces heating costs but also significantly improves air quality.